Seeking transformation through information technology strategies for Brazil, China, Canada and Sri Lanka - Hanna, Nagy; Knight, Peter T. (Innovation, technology, and knowledge management., 2011)
The ability to harness Information Communication Technologies (ICTs) is increasingly at the heart of national competitiveness and sustainable development. As countries seek a way out of the present period of economic contraction, they are trying to weave ICT into their development strategies, in the same way enterprises have learned to use ICT to transform their business models and strategies. This integration offers a new path to development that is responsive to the challenges of our times. In Seeking Transformation Through Information Technology, Nagy Hanna and Peter Knight provide a framework for assessing the opportunities, challenges, and prospects for e-transformation. Featuring contributions from country experts, the editors and authors provide in-depth case studies of ICT deployment in Brazil, China, Canada, and Sri Lanka, and asses the progress of such efforts. The result is an essential resource for academic researchers, policy analysts, policymakers, and industry leaders interested in the role of ICT in national development, innovation, and economic growth.